Problems of Thematic Progression Patterns of English Students’ Academic Writing: A View from Systemic Functional Linguistics - Khorina, Mulyati; Dewiyanti, Sri; Nugraha, Danny Gandana; Sembiring, Bahtera (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2024)
The purpose of this study is to investigate the problems Thematic Progression patterns found in academic writing of English students of Politeknik Negeri Bandung. The method applied in this study was qualitative one with descriptive analysis. The data were taken from English students’ final project reports, focusing on background section. The data were analyzed by using textual analysis of Systemic Functional Linguistics. The results show that there three types of problems related with Thematic Progression patterns. The problems are brand new theme, empty rheme, and confusing selection of textual theme. These findings have implication on academic writing, especially how to develop ideas in academic writing to make it cohesive and coherence.